Comparing the Effectiveness of Compassion Focused Therapy and Mindfulness-Based Cognitive Therapy on the Anxiety of Infertile Women - Heidari , Fatemeh; Ahadi, Hasan; Tajeri , Biuok (Applied Family Therapy Journal (AFTJ), 2023)
Aim: Infertile women face a lot of anxiety in life, and it seems that treatments derived from the third wave of psychotherapy can be effective in reducing their anxiety. As a result, the aim of this study was comparing the effectiveness of compassion focused therapy and mindfulness-based cognitive therapy on the anxiety of infertile women. Methods: The present research in terms of purpose was applied and in terms of implementation method was semi-experimental with a pretest, posttest and two month follow-up plan with the control group. The research population consisted of infertile women who referred to clinics with a fertility specialist of Tehran city in 2022 year. The research sample was 45 people who were selected by purposive sampling method after checking the inclusion criteria and randomly divided into three equal groups including two experimental groups and one control group. Each of the experimental groups underwent eight sessions of 90-minute the therapies of compassion focused and mindfulness-based cognitive, separately and the control group during this time did not receive therapy. The data were collected with Beck et al's anxiety inventory (1988) and analyzed with mixed variance analysis and Bonferroni post hoc test in SPSS software. Results: The analyzes showed that both compassion focused therapy and mindfulness-based cognitive therapy in compared to the control group reduced the anxiety of infertile women, and the effectiveness of compassion focused therapy in compared to mindfulness-based cognitive therapy was more effective in reducing their anxiety (P